Communal roosting behavior and winter diet of the white-tailed kite (Elanus leucurus) in an agricultural habitat on the Argentine pampas - Sarasola, José Hernán (2010)
Although the White-tailed Kite (Elanus leucurus) is widely distributed throughout the Americas, winter communal roosting has been recorded only in the Nearctic portion of its range. As a result, data on the food habits of the White-tailed Kite in South America during the nonbreeding season are scarce and, when available, limited to pellets from solitary individuals. Here, we report the communal roosting behavior and the winter diet of White-tailed Kites in an agricultural habitat on the Argentine pampas based on information gathered over three consecutive years (20062008). From May to July of each year, we observed an average of 11 (±SD 2.8) kites roosting in a grove of Eucalyptus viminalis. Prior to roosting, kites gathered in a tall, dead, and leafless Eucalyptus tree before flying to more densely foliated trees where they spent the night. The diet of kites during winter was composed almost entirely of small mammals, mainly Calomys sp. and Akodon azarae. Because agricultural intensification in the Argentine pampas is ongoing, further studies are needed to gain a complete knowledge of White-tailed Kites in this habitat and of the effects of land-use changes on their foraging and other behavior. © 2010 The Raptor Research Foundation, Inc.